2011
DOI: 10.1002/glia.21164
|View full text |Cite
|
Sign up to set email alerts
|

H‐ferritin is the major source of iron for oligodendrocytes

Abstract: There is a critical relationship between oligodendrocyte development, myelin production, and iron bioavailability. Iron deficiency leads to hypomyelination both in humans and animal models, and the neurological sequelae of hypomyelination are significant. Therefore, understanding molecular mechanisms of iron import into oligodendrocytes is necessary for devising effective strategies for iron supplementation. Although transferrin has been considered as an essential component of oligodendrocyte media in culture,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
85
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 44 publications
3
85
0
Order By: Relevance
“…CSF ferritin was noted to be higher during the first time point assessed (17±10 h), whereas sCD163 was higher during the second time point (72±15 h). This could be consistent with early release of ferritin from damaged and activated microglia (24) or oligodendrocytes (25), with a later increase in sCD163 from systemic, infiltrating macrophages or perivascular microglia scavenging hemoglobin (26). A clinical study has shown early increases (<12 h) in ferritin within contusions after TBI in humans (27), whereas experimental data suggest a more delayed increase (72–96 h) in CD163-positive macrophages/microglia after TBI in rats (28).…”
Section: Discussionsupporting
confidence: 54%
“…CSF ferritin was noted to be higher during the first time point assessed (17±10 h), whereas sCD163 was higher during the second time point (72±15 h). This could be consistent with early release of ferritin from damaged and activated microglia (24) or oligodendrocytes (25), with a later increase in sCD163 from systemic, infiltrating macrophages or perivascular microglia scavenging hemoglobin (26). A clinical study has shown early increases (<12 h) in ferritin within contusions after TBI in humans (27), whereas experimental data suggest a more delayed increase (72–96 h) in CD163-positive macrophages/microglia after TBI in rats (28).…”
Section: Discussionsupporting
confidence: 54%
“…We found ferritin heavy chain, which is expressed abundantly in oligodendrocytes [66] , to be downregulated following poly(I:C). These findings are consistent with the possibil-ity that prenatal inflammation may act to reduce iron availability and so contribute to myelin dysregulation.…”
Section: Discussionmentioning
confidence: 90%
“…Ferritin molecules trafficked across the BBB may be sequestered by oligodendrocytes which accumulate ferritin during postnatal ontogenesis [1]. Oligodendrocytes, which largely utilize FHC [156], may use the ferritin-iron for the synthesis of myelin [2]. Peak myelination by oligodendrocytes occurs at P15, shortly after ferritin trafficking across the BBB ceases [10, 157].…”
Section: Proteins Involved In the Efflux Of Iron From Bmvecmentioning
confidence: 99%